2022
DOI: 10.1093/hmg/ddac192
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous variants in SIX3 and POU1F1 cause pituitary hormone deficiency in mouse and man

Abstract: Congenital hypopituitarism is a genetically heterogeneous condition that is part of a spectrum disorder that can include holoprosencephaly. Heterozygous mutations in SIX3 cause variable holoprosencephaly in humans and mice. We identified two children with neonatal hypopituitarism and thin pituitary stalk who were doubly heterozygous for rare, likely deleterious variants in the transcription factors SIX3 and POU1F1. We used genetically engineered mice to understand the disease pathophysiology. Pou1f1 loss of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…development (Carreno et al, 2017;Crane-Smith et al, 2021;Hamdi-Rozé et al, 2020;Zhao et al, 2012). Recent research also found that mice heterozygous for Six3 displayed a similar pituitary-restricted phenotype due to Six3's control of Shh in the ventral forebrain (Bando et al, 2023). Hence, a SHH signaling defect in the ventral diencephalon leads to the persistence of the diverticulum of Rathke's pouch in Shh +/− .…”
Section: Discussionmentioning
confidence: 99%
“…development (Carreno et al, 2017;Crane-Smith et al, 2021;Hamdi-Rozé et al, 2020;Zhao et al, 2012). Recent research also found that mice heterozygous for Six3 displayed a similar pituitary-restricted phenotype due to Six3's control of Shh in the ventral forebrain (Bando et al, 2023). Hence, a SHH signaling defect in the ventral diencephalon leads to the persistence of the diverticulum of Rathke's pouch in Shh +/− .…”
Section: Discussionmentioning
confidence: 99%